Mesenchymal Stem Cells - Basics and Clinical Application I - Weyand, Birgit (Advances in biochemical engineering, biotechnology, 2013)
A. HarichandanK. SivasubramaniyanH.-J. BühringProspective Isolation and Characterization of Human Bone Marrow-Derived MSCsChristina BendaTing ZhouXianming WangWeihua Tian Johannes GrillariHung-Fat TseRegina Grillari-VoglauerDuanqing PeiMiguel A. EstebanUrine as a Source of Stem Cells Sven KinzebachKaren BiebackExpansion of Mesenchymal Stem/Stromal Cells under Xenogenic-Free Culture Conditions Danielle Minteer Kacey G MarraJ Peter RubinAdipose-Derived Mesenchymal Stem Cells: Biology and Potential Applications Antonina LavrentievaTim HatlapatkaAnne NeumannBirgit WeyandCornelia Kasper Potential for Osteogenic and Chondrogenic Differentiation of MSCLetizia FerroniChiara Gardin Ilaria ToccoRoberta EpisAlessandro CasadeiVincenzo VindigniGiuseppe MucciBarbara ZavanPotential for Neural Differentiation of Mesenchymal Stem Cells Thomas DittmarFrank EntschladenMigratory Properties of Mesenchymal Stem CellsStefania BrunoFederica Collino, Ciro TettaGiovanni CamussiDissecting Paracrine Effectors for Mesenchymal Stem Cells Yin XiaoJiezhong ChenProteomics Approaches in the Identification of Molecular Signatures of Mesenchymal Stem CellsRichard Schäfer Does the Adult Stroma Contain Stem Cells?